Optimization of Unnicked β2-Glycoprotein I and High Avidity Anti-β2-Glycoprotein I Antibodies Isolation - Andrej Artenjak; Adrijana Leonardi; Igor Križaj; Aleš Ambrožič; Snezna Sodin-Semrl; Borut Božič; Saša Čučnik (Journal of Immunology Research)
Patient biological material for isolation of β2-glycoprotein I (β2GPI) and high avidity IgG anti-β2-glycoprotein I antibodies (HAv anti-β2GPI) dictates its full utilization. The aim of our study was to evaluate/improve procedures for isolation of unnicked β2GPI and HAv aβ2GPI to gain unmodified proteins in higher yields/purity. Isolation of β2GPI from plasma was a stepwise procedure combining nonspecific and specific methods. For isolation of polyclonal HAv aβ2GPI affinity chromatographies with immobilized protein G and human β2GPI were used. The unknown protein found during isolation was identified by liquid chromatography electrospray ionization mass spectrometry and the nonredundant National Center for Biotechnology Information database. The average mass of the isolated unnicked purified β2GPI increased from 6.56 mg to 9.94 mg. In the optimized isolation procedure the high molecular weight protein (proteoglycan 4) was successfully separated from β2GPI in the 1st peaks with size exclusion chromatography. The average efficiency of the isolation procedure for polyclonal HAv anti-β2GPI from different matrixes was 13.8%, as determined by our in-house anti-β2GPI ELISA. We modified the in-house isolation and purification procedures of unnicked β2GPI and HAv anti-β2GPI, improving the purity of antigen and antibodies as well as increasing the number of tests routinely performed with the in-house ELISA by ~50%.